Serum IgG4 level during initial treatment as a predictor of relapse in IgG4-related disease. - Su Jin Choi; Soo Min Ahn; Ji Seon Oh; Seokchan Hong; Chang-Keun Lee; Bin Yoo; Yong-Gil Kim (PLoS ONE, 2023)
Introduction We aimed to investigate the predictors of relapse in immunoglobulin G4-related disease (IgG4-RD), focusing on the serum IgG4 levels during initial treatment. Methods We retrospectively recruited 57 patients with IgG4-RD who were treated with immunosuppressants and elevated serum IgG4 levels in a tertiary hospital between January 2011 and December 2020. They were followed up for ≥ 6 months after initiation of immunosuppressive therapy. Clinical and laboratory findings including serum IgG4 levels (reference value: 6-121 mg/dL) were compared between relapsed (n = 13) and non-relapsed (n = 44) groups. Multivariate Cox regression analysis was used to assess the predictors for relapse. We performed a Kaplan-Meier analysis with a log-rank test to evaluate the cumulative relapse rate for two years. Results Median serum IgG4 levels at baseline were 321 mg/dL in the relapsed group and 299 mg/dL in the non-relapsed group. Serum IgG4 levels were normalized after six months in five (38.5%) relapsed and 28 (63.6%) non-relapsed patients. In multivariate Cox regression analysis, the normalization of serum IgG4 levels at six months was associated with a lower risk of relapse, with a hazard ratio of 0.232 (p = 0.019). Central nervous system involvement was associated with the relapse, with a hazard ratio of 21.130 (p = 0.015). The cumulative relapse rate for two years was lower in the normal serum IgG4 group at six months than in the elevated serum IgG4 group at six months (p = 0.027). Conclusion Our study suggests that normalization of serum IgG4 levels during immunosuppressive treatment for IgG4-RD independently predicts relapse-free outcomes. Thus, monitoring serum IgG4 levels might be used as a marker of prognosis.